UJI AKTIVITAS ANTIHIPERGLIKEMIA TEH BUNGA KECOMBRANG (Etlingera elatior (Jack.) R.M.Sm ) TERHADAP MENCIT PUTIH (Mus Musculus) JANTAN DENGAN METODE TOLERANSI GLUKOSA - Herdaningsih, Sulastri; Nurhafizah; Hairunnisa (Jurnal Komunitas Farmasi Nasional, 2025)
Diabetes mellitus is a metabolic disorder caused by pancreatic dysfunction, characterized by elevated blood glucose levels due to decreased insulin production by pancreatic beta cells. This study aimed to evaluate the antihyperglycemic activity of torch ginger tea (Etlingera elatior (Jack.) R.M.Sm.) in male white mice (Mus musculus) using the glucose tolerance method. The mice were divided into control and treatment groups, receiving torch ginger tea at doses of 1,25 gram/KgBW, 2,5 gram/KgBW, and 5 gram/KgBW. The tea was administered orally, followed by glucose induction 30 minutes later. Blood glucose levels were measured over 4 hours at 30-minute intervals. Statistical analysis showed significant differences between the treatment groups and the negative control at all tested doses (p = 0.00; p < 0.05). These results indicate that torch ginger tea at doses of 1,25 gram/KgBW, 2,5 gram/ KgBW, and 5 gram/KgBW exhibits antihyperglycemic activity in male white mice (Mus musculus) based on the glucose tolerance method.